2018
DOI: 10.1042/bsr20171496
|View full text |Cite
|
Sign up to set email alerts
|

20-Hydroxyeicosatetraenoic acid antagonist attenuates the development of malignant hypertension and reverses it once established: a study in Cyp1a1-Ren-2 transgenic rats

Abstract: We hypothesized that vascular actions of 20-hydroxyeicosatetraenoic acid (20-HETE), the product of cytochrome P450 (CYP450)-dependent ω-hydroxylase, potentiate prohypertensive actions of angiotensin II (ANG II) in Cyp1a1-Ren-2 transgenic rats, a model of ANG II-dependent malignant hypertension. Therefore, we evaluated the antihypertensive effectiveness of 20-HETE receptor antagonist (AAA) in this model. Malignant hypertension was induced in Cyp1a1-Ren-2 transgenic rats by activation of the renin gene using ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…The infarct size was normalized to the area at risk. This approach has been validated in many experimental studies and is currently accepted as the "gold standard" for measurement of myocardial infarct size in small animals (Sanada et al, 2011). The incidence and severity of ventricular arrhythmias during the 20-min ischemia and first 3 min of reperfusion were assessed according to the Lambeth Conventions (Walker et al, 1988).…”
Section: Experimental Design-seriesmentioning
confidence: 99%
See 1 more Smart Citation
“…The infarct size was normalized to the area at risk. This approach has been validated in many experimental studies and is currently accepted as the "gold standard" for measurement of myocardial infarct size in small animals (Sanada et al, 2011). The incidence and severity of ventricular arrhythmias during the 20-min ischemia and first 3 min of reperfusion were assessed according to the Lambeth Conventions (Walker et al, 1988).…”
Section: Experimental Design-seriesmentioning
confidence: 99%
“…This therapy has become a "golden standard" in the treatment since the 1970s (Ginks et al, 1972;Maroko et al, 1972). On the other hand, restoration of coronary artery blood flow may cause cardiomyocyte death and microvascular dysfunction and worsen tissue damage; this phenomenon is termed "myocardial ischemia/reperfusion (I/R) injury" (Sanada et al, 2011;Jennings, 2013). The exact mechanisms of I/R injury are not fully understood but it may paradoxically diminish the beneficial effects of myocardial reperfusion.…”
Section: Introductionmentioning
confidence: 99%
“…EET-A [disodium (Z)-(13-(3-pentylureido) tridec-8-enoyl)- l -aspartate], a 14,15-EET analog, was given in drinking water, and its concentration was adjusted in such a way that the daily dose was either 10 mg/kg/day (EET-A) or a high dose of 40 mg/day/kg (EET-A HD). 20-HETE receptor antagonist {disodium [(6Z,15Z)-20-hydroxyeicosa-6,15-dienoyl]- l -aspartate; AAA} was also given in drinking water at a concentration adjusted to yield a daily dose of 10 mg/kg/day, based on our recent studies ( Gangadhariah et al, 2014 ; Sedláková et al, 2018 ; Gawrys et al, 2020a ). The EET-A and AAA were designed and synthesized in the laboratory of JRF.…”
Section: Methodsmentioning
confidence: 99%
“…20-HETE is a very unique AA metabolite with both pro- and antihypertensive activities ( Nowicki et al, 1997 ; Ward et al, 2004 ; Wu et al, 2014 ). Interestingly, both the stimulation of its production ( Jíchová Š et al, 2016 ) and the inhibition of its action ( Sedláková et al, 2018 ) can cause beneficial effects. Moreover, we have recently shown that, after acute infusion of both compounds, a significant improvement in renal hemodynamics is observed, with a subsequent reduction in blood pressure ( Walkowska et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, 14,15-EET analog, disodium (S)-2-(13-(3-pentyl)ureido)-tridec-8(Z)-enamido)succinate (EET-A; 5 mg/kg) or N-disodium succinate-20-hydroxyeicosa-6(Z),15(Z)-diencarboxamide (AAA;10 mg/kg) were given, alone or combined. The dose of EET-A was determined in preliminary experiments and the AAA dose was validated earlier ( Sedláková et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%